A Technical System for the Large-Scale Application of Metabolites From Paecilomyces variotii SJ1 in Agriculture - Wang, Qingbin; Peng, Chune; Shi, Liran; Liu, Zhiguang; Zhou, Dafa; Meng, Hui; Zhao, Hongling; Li, Fuchuan; Zhang, Min (Frontiers in Bioengineering and Biotechnology, 2021)
Compared with endophytes, metabolites from endophytes (MEs) have great potential in agriculture. However, a technique for industrializing the production of MEs is still scarce. Moreover, the establishment of effective methods for evaluating the quality of MEs is hampered by the fact that some compounds with beneficial effects on crops have not been clearly identified. Herein, a system was established for the production, quality control and application of MEs by using the extract from Paecilomyces variotii SJ1 (ZNC). First, the extraction conditions of ZNC were optimized through response surface methodology (RSM), after which each batch (500 L) met the consumption requirements of crops in 7,467 hectares. Then, chromatographic fingerprinting and enzyme-linked immunosorbent assay (ELISA) were applied to evaluate the similarity and specificity of unknown effective components in ZNC, ensuring a similarity of more than 90% and a quantitative accuracy of greater than 99.9% for the products from different batches. Finally, the bioactivity of industrially produced ZNC was evaluated in the field, and it significantly increased the potato yields by 4.4-10.8%. Overall, we have established a practical technical system for the large-scale application of ZNC in agriculture.